(untitled) - David S. Kidwell (Orlando, Florida, 1997)
The book introduces the basic concepts and vocabulary necessary to understand the operation of financial system. It provides a comprehensive introduction to interest rates, bond pricing, bon yields, and interest rate risk. It describes the major financial markets in which financial institutions participate. It focuses on the management of commercial banks and the regulation of financial institutions. It describes important nonbank financial intermediaries in the nation's economy; and discusses issues that are of important to contemporary managers of financial institutions
Keywords: Financial institutions, international,Managerial economics